PROBLEMATIKA YURIDIS LEGISLASI SYARIAT ISLAM DI PROVINSI NANGROE ACEH DARUSSALAM - Muh Fauzi (Al-Ahkam, 2012)
Nanggroe  Aceh  Darussalam  (NAD)  in  the  reform  era  is authorized  returned  to implement  Sharīah (Islamic law). Its authority is justified by the l egal basis: Law No. 44 of 1999 on Privileges of Aceh, Law No. 18 of 2001 on Special Autonomy for the Province of Aceh as Nanggroe Aceh Darussalam, and Law No. 11 of2006 regarding the Government of Aceh. From this legal basis, then followed by the formulation of regulations ( Qānūn) at the  provincial  level.  But  legislation  of  implementi ng  shari'ah  law  in  NAD  contains problematic juridical. For instance: determining ofsanctions, in the form of whipping and one or two years imprisonment, considered against legislation in higher level. Another problem is that Syar'iyyah Court positions still below on the Supreme Court (MA) as the highest court. The efforts to open “special room” of Supreme Court in NAD is seen as a solution not to take it below on the Supreme Court, seen a contrary to the laws and regulations  are  higher.  Likewise,  the  competence  of  Syar'iyyah  Court  particularly  in handling a criminal cases is still obscure and there is a clash with the competence of the District Court.***Provinsi  Nanggroe  Aceh  Darussalam  (NAD)  pada  era  reformasi  diberi  kewenangan kembali untuk melaksanakan syariat Islam. Kewenangan ini dilandaskan pada payung hukum berupa UU No. 44 Tahun 1999 tentang Keistimewaan Aceh, UU No. 18 Tahun 2001 tentang Otonomi Khusus bagi Provinsi Daerah Istimewa Aceh sebagai Provinsi Nanggroe Aceh Darussalam, dan UU No. 11 Tahun 2006 tentang Pemerintahan Aceh. Payung hukum tersebut kemudian ditindaklanjuti dengan pembuatan Perda atau Qānūnpada tingkat Provinsi NAD. Namun legislasi pelaksanaan syariat Islam di Provinsi NAD mengandung problematika yuridis. Penentuan bentuk sanksi berupa cambuk dan kadar sanksi  berupa  penjara  1  (satu)  atau  2  (dua)  tahun  b ertentangan  dengan  peraturan perundang-undangan  yang  lebih  tinggi.  Problem  lain  adalah  masih  bertumpunya peradilan  Mahkamah  Syar‘iyyah  pada  Mahkamah  Agung  (MA)  sebagai  puncak  peradilan. Upaya pembukaan “kamar khusus” MA di Provin si NAD yang dipandang sebagai solusi agar tidak bertumpu pada MA, justru bertenta ngan dengan peraturan perundangundangan  yang  lebih  tinggi.  Demikian  juga,  kompetensi  Mahkamah  Syar‘iyyah khususnya dalam menangani perkara pidana masih kabur dan terjadi benturan dengan kompetensi Pengadilan Negeri.***Keyword: syariat Islam, Provinsi NAD, Mahkamah Syar’iyyah, yuridis